Penentu Kecukupan Modal Bank yang Terdaftar di BEI - Malik, Abdul (Graha Akuntansi, 2021)
This study aimed to examine the effect of non-performing loans, loan-deposit ratio, return on assets, size of the adequacy of capital. This research conducted by using secondary data. Population in this study was conducted with less using secondary data. Population in this research is the company commercial bank listed on the stock exchange Indonesia from 2010-2014. This sampel retrieval metho by using purposive sampling. There are 16 commercial banks company studied. This tudy uses multiple methods of analysis regression. Studies show that non-performing loan and no significant negative effect on capital adequacy, loan-deposit ratio and significant negative effect on capital adequacy, return on assets and a significant positive effect on capital adequacy, size and significant positive effect on capital adequacy. Adjusted R square value is 0,419 this means that 41,9% dependent variable can be explained by the independent variable, while the remaining 58,1 % is explained by the variable-orher variables outside the research model.